Keabsahan Klausula Baku dalam Perjanjian Pembiayaan Modal Ventura dalam Perspektif Asas Kebebasan Berkontrak - Zahra Suryandaru; Yudho Taruno Muryanto (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
Venture capital financing agreements are agreements that often contain standard clauses prepared unilaterally by Venture Capital Company. This research analyzes the principle of freedom of contract in venture capital financing agreements that include standard clauses, with the aim of assessing their validity. This research uses normative law method with statutory and conceptual approaches. The results show that standard clauses in venture capital financing agreements aim to provide efficiency and legal certainty, but have the potential to create an imbalance in the bargaining position between Venture Capital Companies and Investee Company. Venture capital financing agreements that include standard clauses are invalid because the subjective requirements in the agreement are not met and are contrary to the principle of freedom of contract and the principle of good faith in Article 1338 paragraph (3) of the Indonesian Civil Code which states that agreements must be carried out in good faith. So that firmer regulations and protection mechanisms for weaker parties in the agreement are needed to ensure that the principle of freedom of contract continues to run fairly.